The Review of Entrepreneurship Interest for Student at Class XII SMKN 1 Padang Based on Parents Occupation Background - 1019-1039 , Della Dwiyana (Universitas Negeri Padang, 2016)
ABSTRACTThis research was descriptive research that purposed to find out the entrepreneurship interest for student at class XII SMKN 1 Padang and revealed parents occupational background that gave highest outcome in entrepreneurship subject. In this research, there was one single variable which was entrepreneurship interest.Research population was students of class XII SMKN 1 Padang year of school 2015/2016 which amounted to 330 students. Sample was taken by simple random sampling and Taro formula which was amounted to 181 students. Data collection technique was distribution of questionnaire with Likert scale as instrument assessment. Parents occupational data was obtained from student’s enrollment data. Parents occupational was consisted of seven occupational types which were entrepreneur, public services/police/army, private sector, laborer, famer, fisherman, and others. Data analysis was frequency distribution analysis and average score analysis. Research finding shows that all parents occupation backgrounds give subtends an interest of entrepreneurship. The highest average score of parents occupational background that gives entrepreneurship interest is occupation of entrepreneur. Keywords: Entrepreneurship Interest, Parents Occupation